1993
DOI: 10.1002/j.0022-0337.1993.57.9.tb02789.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of dental students' belief in the right to refuse treatment to HIV‐positive patients

Abstract: We examined predictors of dental student's belief that they should be allowed to refuse treatment to HIV‐infected persons. We surveyed 181 first; second‐, and fourth‐year dental students at a large urban university using a 44‐item, self‐administered anonymous questionnaire and a measure of dispositional optimism. Several composite measures were created and their relationship to belief in the right to refuse treatment was assessed. Regression techniques were used to describe the relationship between the depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Our study is similar to two other studies which found no significant difference in attitudes towards HIV/AIDS between first and fourth year dental students, suggesting that increased professional knowledge does not lead to increased acceptance (39, 40).…”
Section: Discussionsupporting
confidence: 90%
“…Our study is similar to two other studies which found no significant difference in attitudes towards HIV/AIDS between first and fourth year dental students, suggesting that increased professional knowledge does not lead to increased acceptance (39, 40).…”
Section: Discussionsupporting
confidence: 90%
“…Current guidelines are that dentists must not refuse to treat a patient solely on the grounds of HIV infection and they cannot legally refer these patients to specialty clinics for routine dental care. Some of the reasons that dentists are afraid of treating these patients and refer them to other dentists are as follows: lack of ethical responsibility; fear among staff members in the dental operatory; concerns related to uncertainty regarding safety regulations; cost of infection‐control procedures; lack of knowledge regarding oral lesions associated with HIV; and loss of patients uninfected with HIV as a result of treating HIV‐positive patients.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies published between 1988 and 1997, involving dental students and dental hygiene students documented that students exhibited bias towards individuals with AIDS as well as a more generalised homophobia. Several studies have been conducted to assess the willingness of oral health professionals to treat HIV‐positive individuals, either as a main survey or as part of a knowledge, attitudes and practice survey, in many parts of world, such as Brazil, Mexico, Jordan and Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Using binary regression, the determinants of refusal to treat herpes labialis patients were marital status and attitude toward herpes labialis. This can be explained by the fact that non-professional attitudes, low optimism scores, and low comfort levels were among the best predictors of belief in the right to refuse treatment to HIV-infected patients [ 33 ]. Reducing concerns and enhancing providers’ comfort levels with respect to caring for patients with herpes labialis can help to reduce the tendency to refuse treatment to these patients.…”
Section: Discussionmentioning
confidence: 99%